Buoyant Capital Spending and Worries over Real Appreciation : Cold Facts from Algeria - Diallo, Oumar (IMF Working Papers; Working Paper ;, 2007)
The Government of Algeria has pursed a relatively expansionary fiscal policy in recent years, thanks to rising oil prices and revenues. The paper explores the potential effects of such a stance on real exchange rate and uncovers a relatively small appreciating effect of increased government capital expenditure. This is explained by the fact that a significant share of capital spending falls into tradable imported goods. However, the envisaged increase in capital spending, if well designed and implemented, might in the long-run translate into rising operations and maintenance expenditure-mostly nontradable goods-thereby causing a higher real appreciation. This implies that Algeria should carefully consider the implications of its public investment program on recurrent expenditure.